The Chemistry of Peace - Dow Chemical Company (1938)
Color print magazine advertisement for the Dow Chemical Company featuring a peaceful town on a snowy winter night. The accompanying text details so-called "peaceful" applications for Dow products, including Dowflake Chemical Chloride to improve road conditions and synthetic solvents to improve dry cleaning services.
Keywords: Chemical industry; Dow Chemical Company; Corporations; Advertising; Advertising, Industrial